2008
DOI: 10.1111/j.1365-2648.2008.04747.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported competence of home nursing staff in Finland

Abstract: Simple and practical ways for updating the competence of home nursing staff should be created. These staff are a very important source of information for home care clients. Supporting the knowledge of home nursing staff is also an efficient way of keeping clients and their informal caregivers informed about care guidelines, health and social services and social benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 50 publications
5
23
1
1
Order By: Relevance
“…Other reasons are a heavy workload and lack of economic resources for competence development. According to other studies, Löfmark and Torell-Ekstrand, Wallin et al, and Boström et al, 22,23,15 RNs have a negative attitude to searching for and making use of evidence-based knowledge. Their competence is thought to be traditional and routinized.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other reasons are a heavy workload and lack of economic resources for competence development. According to other studies, Löfmark and Torell-Ekstrand, Wallin et al, and Boström et al, 22,23,15 RNs have a negative attitude to searching for and making use of evidence-based knowledge. Their competence is thought to be traditional and routinized.…”
Section: Discussionmentioning
confidence: 96%
“…Several different categories of staff care for the person during the day, at night, and at weekends, and comprehensive, computer-based documentation is therefore crucial. As each RN is responsible for providing care to a large number of persons (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and there is no time for RNs to visit all of them every day, documentation is important. After the first visit RNs prepare an individual care plan, which is carefully documented, and this plan is then supposed to be followed up and implemented by the ENs.…”
Section: Nursing Content In Home Carementioning
confidence: 99%
“…Self-perceived competence did not differ between the different educational levels. Similarly, a previous study found that educational level did not predict self-perceived competence among home care staff (Grönroos, & Perälä, 2008). Self-assessment of competence is valued in nursing (Fereday & Muir-Cochrane, 2006), Nonetheless, the concept of competence is ill defined, and it has been argued that nurses cannot judge what they ought to know and what they do and do not know (Cowan, Norman, & Coopamah, 2005).…”
Section: (7)mentioning
confidence: 96%
“…All 21 items of CCCS showed sufficient and significant loading for the 1‐factor model. In comparison to previous studies on development of community care competence, many did not evaluate the psychometric properties (Grönroos & Perälä, ; Hasson & Arnetz, ). In studies that reported good psychometric properties, they were developed for post‐registered nurses.…”
Section: Discussionmentioning
confidence: 98%
“…Other lengthy scales include the 138‐item scale assessing community health nurses’ learning needs by Akhtar‐Danesh et al, () and 176‐item scale measuring palliative competencies by Slatten et al, (), which have been reported to yield low response rates of 47%–50%, respectively. Evidence on the reliability and validity of some scales has not been reported (Grönroos & Perälä, ; Josefsson & Hansson, ). Although the nursing older people—competence evaluation tool scale developed by Bing‐Jonsson, Hofoss, Kirkevold, Bjork, and Foss () has shown evidence of reliability and validity, it is targeted to assess the competencies of community‐based nursing staff and only focuses on caring for the elderly people.…”
Section: Introductionmentioning
confidence: 99%